The Contribution of Fish Farming to the Socio-Economic Status of Fish Farmers in Ebonyi State, Nigeria (Global Journal of Science Frontier Research, 2025)
This study investigated the contribution of fish farming to the socio-economic status of fish farmers in Ebonyi State, Nigeria. Multi-stage sampling techniques was used and 96 farmers were chosen at random. Structured questionnaires were used to collect data, which was then analyzed using descriptive statistics and multiple regression models. The results of socioeconomic characteristics revealed that the majority of fish farmers (82.3%) were male, married (62.5%), well-educated, and between the ages of 31 and 40 (43.8%). Benefits derived and constraints faced by farmers had a significant influence on their socio-economic status at p≤0.025 and p≤0.007 respectively.
Keywords: benefits-derived; contribution; ebonyi State; fish farming; Nigeria; Socio-economic status